Seroprevalence Study of Brucellosis in Rams of Sulaimani region: Talib Ghaidan Mannt Ali, Faridoon Abdul sattar Mahamed Amin and Rebwar Bahir Ahmed - Mannt Ali, Talib Ghaidan (The Iraqi Journal of Veterinary Medicine, 2019)
The aim of our study is to detect the incidence of Brucella infection in rams in Sulaimani region by using Rose Bengal, 2 Mercaptoethanol and indirect ELISA tests. The following research was conducted on 253 rams in different fields of sheep they were distributed in eight districts, represented by Pebaz (12 ram), Chamchmal (53 ram), Barika (32 ram), Damrkan (27 ram), Qalghanlw (41 ram), Darbasara (26 ram) , Dawye (38 ram) and Bazian (24 ram). Blood samples were collected from jugular vein. All blood samples were proceeds for sera preparation in veterinary teaching hospital / college of veterinary medicine / university of Sulaimani. Out of 253 rams 61 (24.11%) and 192(75.89%) were positive and negative for brucellosis respectively during Rose Bengal test. All rams showed the infection by brucellosis throughout the titer of antibodies. The serological test by 2 mercaptoethanol used for distinguishes the acute and chronic infection by assessment the titer of IgG and IgM antibodies. A percentage of 51(83.61%) and 10(16.39) for acute and chronic infection of brucella respectively were recorded. The results by iELISA manifested rams in all field 42(68.8%) were positive while 19(13.15%) were negative. The research showed 18(29.50%) of rams were manifestation the clinical signs represented by epididymitis, hyperthermia and orchitis. Static analysis revealed there is no significant (P-value<0.05) differences between iELISA and 2ME test. Our conclusion from this study confirmed that this disease of brucella is endemic in province of Sulaimani; in addition the disease is spread in the flock of sheep via sexual contact during mating. Control of the diseases must be implement a global program represented by vaccination as well as transfer of animals and eliminate the infected ram from the herds.